Impact of Nursing Education and a Monitoring Tool on Outcomes in Traumatic Brain Injury - Gamble, Miriam; Luggya, Tonny Stone; Mabweijano, Jacqueline; Nabulime, Josephine; Mowafia,Hani (African journal of emergency medicine, 2020)
Throughout the world, traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality. Low-and middle-income countries experience an especially high burden of TBI. While guidelines for TBI management exist in high income countries, little is known about the optimal management of TBI in low resource settings. Prevention of secondary injuries is feasible in these settings and has potential to improve mortality.